The Effect of Aluminum and Stainless Steel Thickness on the Absorption of X-Ray Radiation Dose of the Betatron SEA-7 Machine - Totok Dermawan; Ismail; Azhar Zakiyah (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
Radiographic contrast is the difference in brightness in a film image, due to differences in the object’s absorption capacity for X-rays, which affects the quality of the radiographic image. Gray value is a substitute for the density of conventional radiographic film which is viewed and evaluated using a computer, to obtain a visual perception of image contrast and noise to measure the quantity of radiation that penetrates a certain area. Acceptance Value Minimum X-ray density refers to ASME Standards. The CRx gray value is 28800 minimum and 64000 maximum [1]. In the use of the Betatron Sea-7 machine, to obtain radiographic contrast, it is necessary to add aluminum (Al) or stainless steel (SS) as a filter layer. The method involves irradiating a steel material target with a thickness of 25 mm with 5 MeV energy with a dose of 35 R, either using or without a layer of Al or SS material, then analyzed using the Rhythm Review Application. The results obtained, for stainless steel, the density received at a thickness of 3 mm, 6 mm, and 9 mm, for aluminum a thickness of 3 mm. With this energy and dosage, stainless steel can be added as a layer in the operation of the Betatron Sea-7 machine to produce a radiographic film quality density that meets ASME standards [2].